Research - It’s not what it used to be - Abd Razak, Dzulkifli (2006)
THE South Korean stem cell research scandal continues to hog the headlines. Last week, the country's top university announced the suspension of Dr Hwang WooSuk and six other professors who helped him fabricate the research. The dean of academic affairs at Seoul National University was quoted as saying: "They are immediately banned from teaching and engaging in research." This, however, may not be the final sanction. The university president had earlier called for "heavy punishment" for those involved in the scientific scandal. In fact, Hwang has confessed to misusing part of the research funds which amounted to more than 35 billion won (RM142 million) showered on him by the Government. In addition, he allegedly made donations to politicians. For all these, Hwang said he was blinded by work and the drive for achievements. The university reportedly is still looking into the misconduct in research and alleged breach of ethical standards.